Forest damage and its braking effect on the extreme snow avalanche on Mt. Nodanishoji, Japan, in 2021 - Yukari Takeuchi; Yuta Katsuyama; Takafumi Katsushima; Hayato Arakawa; Satoru Adachi; Katsuhisa Kawashima (Arctic, Antarctic, and Alpine Research)
An extreme snow avalanche occurred on Mt. Nodanishoji, Japan, in 2021. This avalanche was the second largest ever documented in Japan and destroyed many trees and structures. Despite the increasing interest in avalanche disaster mitigation effects of forests, there are limited opportunities to obtain actual data sets on avalanches and forests. In this study, we reconstructed the avalanche velocity based on the cedar forest damage and simulated the avalanche flow using the dynamical run-out model Titan2D to reveal the avalanche movement and ascertain the braking effect of the forest on the avalanche. We successfully simulated the whole movement of the extreme avalanche with a horizontal runout distance of 2,800 m from the starting zone at an altitude of 1,700 m to the run-out zone considering the effect of the forest by increasing the frictional parameters in the model. Whereas in the case of no forest, the avalanche spread beyond its actual reach, considering the forest, the run-out distance decreased and was consistent with the observed reach. Comparing the results with and without forests, we ascertained the distinct braking effect of the forest on the extreme avalanche and quantify it in terms of a locally increased friction angle.